Make a Match in Arabic Vocabulary Learning at Muhammadiyah School: Pelajari Kosakata Arab di Sekolah Muhammadiyah - Asysyaikhon , Abdulloh Sa’ad; Anwar , Najih (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Mastery of foreign language vocabulary, particularly Arabic, plays a crucial role in supporting students’ linguistic competence and academic development. Specific Background: In Islamic-based schools such as SMA Muhammadiyah 3 Tulangan, vocabulary acquisition often faces challenges due to monotonous teaching methods and limited student engagement. Knowledge Gap: Previous studies have explored cooperative learning strategies, yet limited evidence exists on how the Make a Match method contributes specifically to Arabic vocabulary mastery in the Muhammadiyah school context. Aims: This study aims to investigate the role of the Make a Match method in improving Arabic vocabulary mastery among tenth-grade students. Results: Using a quasi-experimental one-group pretest-posttest design with 26 participants, data were analyzed through a paired sample t-test. Findings revealed a significant improvement, with the mean score increasing from 55.96 to 74.42 and a significance value of 0.000 < 0.05. Novelty: This study provides empirical evidence of the Make a Match method as an interactive and student-centered approach to Arabic learning within Muhammadiyah education. Implications: The results suggest the method can foster active participation, retention, and effective vocabulary acquisition, offering a practical model for Arabic language pedagogy.HIghlights: Significant improvement in Arabic vocabulary mastery Interactive learning fosters student engagement Applicable model for Muhammadiyah schools Keywords: Make a Match, Arabic Vocabulary, Cooperative Learning, Muhammadiyah, Quasi-Experiment